Effect of Reforestation Tree Species on the Distribution and Stability of Purple Soil Aggregates - ZHONG Yujian; HE Feng; HAN Guangzhong; ZHAO Xia; YANG Fan (Shuitu Baochi Xuebao)
[Objective] Afforestation following the Grain for Green initiative is a crucial measure to improve soil structure and reduce soil erosion. Understanding the mechanisms of the effects of afforestation tree species on the formation of soil aggregates can provide valuable insights for soil conservation. [Method] Four types of artificial forests (Cryptomeria fortunei (CF), Cryptomeria fortunei and Betula luminifera (MF), Camellia sinensis (CS), and Neosinocalamus affinis (NA)) established on sloping farmland (SF) (cornfield) in the Rainy Area of Western China after 20 years of afforestation were taken as the research objects, in order to analyze the changes in soil aggregate content and stability after the conversion from farmland to artificial forests. [Results] (1) Compared to the sloping farmland, the artificial forests of MF, CS, and NA significantly increased the soil aggregates >5 mm, but decreasd the 0.5~1 mm soil aggregates (p < 0.05). The dominant soil aggregates shifted from 0.5~1 mm to >5 mm. (2) The soil aggregate parameters, including the geometric mean diameter (GMD), mean weight diameter (MWD), and the content of aggregates of >0.25 mm (R0.25), increased by 46.93%~330.30%, 47.01%~191.03% and 5.02%~19.66%, respectively, in the artificial forests. Conversely, the destruction rate (PAD0.25) and fractal dimension (PSD) decreased by 15.41%~75.09% and 1.65%~9.20%, respectively. These indicators of aggregate stability consistently demonstrated that the stability of soil aggregates in the artificial forests was enhanced, with a specific ranking of CS > NA > MF > CF, indicating that CS and NA were both relatively superior. (3) The content and stability of dominant soil aggregates were extremely significantly positively correlated with the content of NOC, and extremely significantly negatively correlated with the content of soil gravel (p < 0.01). [Conclusion] The weathering of purple soil following afforestation provides the material foundation for aggregate formation, while the humus formed in the soil of artificial forests acts as a binding agent, promoting the formation of large aggregates and the maintenance of their stability.